EFEKTIVITAS HOUSE JOURNAL THE MALL WITH STYLE SEBAGAI MEDIA PROMOSI PADA MALL SKA PEKANBARU - Vici Santa Tynecelia; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The Promotion activity is an important role in reintroduce, renotify, and remind the existence of an agency and the products. One of media which is used in this promotion activity is House Journal. The purpose of this research is to show the effectiveness of House Journal The Mall with Style as the promotion media of SKA Mall Pekanbaru.This research used quantitative method. The population in this research were the readers of House Journal The Mall with Style. The sampling technic was Accidental Sampling used Unknown Population formula which was 96 population. The data collection technique was done by using questioner and interview of the population. The data processing technique used EPIC Model (Emphaty, Persuation, Impact, Communication).The result of the research showed the effectiveness of House Journal The Mall with Style as the promotion media of SKA Mall Pekanbaru, based on EPIC Model, reached effective enough. This was proved by the medium score of emphaty dimension which reached 3,08; persuation dimension reached 3,32; impact dimension reached 3,12 and communication dimension reached 3,74. The EPIC score rate was 3,31 in effective distance (2,61-3,40).Keyword : House Journal, Effectivenes, Promotion Media